Three essays on export credit support and related issues of current system - Pýcha, Mikuláš (2022)
The dissertation is compiled from articles that explore the field of export credit support and its current problems. The whole of the research was motivated by a desire to improve the system or point out issues that should receive more attention. The results are based on both theoretical and practical findings from the world of export credit agencies. During the research, the hypotheses and questions were discussed with multiple representatives of those institutions, which enables us to state that some of the findings could also be used practically in the real world. The main part of the research builds up a macroeconomic methodology to test the adequacy of minimum premium rates in connection to the best practice of applying them to the loan principal amount only while simultaneously insuring interest payments as well. This practice creates a problem that is not widely discussed and which deserves more attention. It creates room for market failures (mostly the moral hazard of insured subjects), may be in conflict with long-term financial sustainability, and does not guarantee a level playing field. Based on the expected loss calculation, the premium rates should be more closely related to the total insured value. Furthermore, the maximum amount of insured interest was researched under the current restriction system, in which the premium rates apply to the loan principal amount only. There is a close relationship between this maximum amount and the rate of return on investments that can be attained by an export credit agency. The dissertation is also enriched by a microeconomic analysis of the motivations for export support, while an explanation of the various goals that commercial companies have is also present. The microeconomic part defines a model in a general form that enables the valuation of export projects before they receive export support.